2022
DOI: 10.1007/s00284-022-02834-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Genomic Analysis of Bacteriophage vB_KpnM_IME346 Targeting Clinical Klebsiella pneumoniae Strain of the K63 Capsular Type

Abstract: A Klebsiella pneumoniae bacteriophage (vB_KpnM_IME346) was isolated from a hospital sewage sample. This bacteriophage specifically infects a clinical K. pneumoniae strain with a K63 capsular polysaccharide structure. The phage genome was evaluated by next-generation sequencing, which revealed a linear double-stranded DNA genome consisting of 49,482 base pairs with a G+C content of 49.1%. The latent period of vB_KpnM_IME346 was shown to be 20 min, and the burst size was 25–30 pfu (plaque-forming units)/infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…To date, Myoviridae phages have not been found to disrupt the hypervirulent K. pneumoniae MLST ST65 with a K2 serotype. Fibronectin is responsible for determining the host specificity of phages ( 1 ), which explains the difference in the serotypes of the host bacteria infected by Myoviridae phages isolated in this study compared with other reports ( 16 , 20 , 21 ). The phylogenetic tree showed that hvKpP3 is a new phage that is distinct from others.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…To date, Myoviridae phages have not been found to disrupt the hypervirulent K. pneumoniae MLST ST65 with a K2 serotype. Fibronectin is responsible for determining the host specificity of phages ( 1 ), which explains the difference in the serotypes of the host bacteria infected by Myoviridae phages isolated in this study compared with other reports ( 16 , 20 , 21 ). The phylogenetic tree showed that hvKpP3 is a new phage that is distinct from others.…”
Section: Discussionmentioning
confidence: 52%
“…All of the annotated CDSs can be further categorized into five modules: (i) DNA replication and regulation (DNA polymerase, HNH endonuclease, deoxyuridine 5′-triphosphate nucleotidohydrolase, and helicase), (ii) lysis (lysozyme), (iii) structural proteins, (iv) DNA packaging (head morphogenesis protein, major capsid protein, tape measure protein, baseplate protein, phage noncontractile tail fiber protein Gp17, tail fiber protein), and (v) other proteins. Studies have shown that DNA polymerase and helicase play important roles in phage replication ( 16 ). Nucleotide BLAST analysis showed that phage hvKpP3 exhibited high DNA similarity (76%) to the KpnM JustaPhage (GenBank accession no.…”
Section: Resultsmentioning
confidence: 99%